Efektivitas Art Therapy dalam Program Bimbingan Terhadap Kreativitas Anak Usia Dini - Wirastania, Aniek; Farid, Dimas Ardika Miftah; Lathifah, Maghfirotul (Universitas Nusantara PGRI Kediri, 2023)
Creativity is an important aspect for every individual and should be developed from an early age. The development of creativity in children can be done by facilitating the use of creative media. This study aims to develop children's creativity by using art therapy in the guidance program. Art therapy in this guidance program is useful in increasing children's creativity through the process in producing a work. The approach used in this study is quantitative with a quasi-experimental design method. This study carried out the steps from the preliminary study, compiling a hypothetical program based on the preliminary study, revising the program, conducting experiments that were carried out for five treatments, and then data organization and data analysis were carried out using the Wilcoxon test. Based on the results of data analysis tests using SPSS 26 software, it was found that the implementation of art therapy in the guidance program was effective in increasing the creativity of playgroup students.